Spatial characteristics and determinants of traditional village distribution in Guizhou Province - Qiuju Mao; Liang Xie; Lai Fan (PLoS ONE, 2025)
This study employs a range of analytical techniques, including the geographical detector, kernel density estimation, imbalance index, geographical concentration index, and nearest neighbor index, all integrated with ArcGIS 10.8, to examine and illustrate the spatial distribution of 757 traditional villages across Guizhou, revealing an aggregated spatial distribution pattern of traditional villages, i.e., “one highly concentrated area and two secondary density clusters.” This pattern is influenced by both natural and socio-cultural factors, with socio-cultural elements such as road network density, GDP, and ethnic minority populations playing a more significant role than natural environmental factors. The results of geodetector analysis indicate that the interaction between these factors generally shows a nonlinear enhancement effect. Based on these findings, this study proposes four main strategies to preserve and enhance traditional villages: (1) establishing regional identities that reflect local ethnic characteristics; (2) improving village infrastructure to enhance accessibility; (3) implementing targeted protection and utilization strategies based on local conditions; and (4) industrial linkage, combining protection and development.